2013
DOI: 10.3109/01443615.2013.829029
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phase-I periodontal therapy on pregnancy outcome in chronic periodontitis patients

Abstract: Recent studies have shown periodontal diseases (gum diseases) as risk factors for adverse pregnancy outcomes, such as prematurity and low birth weight. Objectives of the present study were to determine the effect of non-surgical periodontal therapy on pregnancy outcomes in women with periodontitis and to detect IgM and IgG status in cord blood during delivery. A total of 20 pregnant women in their 2nd trimester and associated with chronic generalised periodontitis were selected and recruited for the study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
0
20
0
2
Order By: Relevance
“…Studies done in this field identified maternal periodontitis as a potential risk factor for preterm birth and low birth weight. [ 5 6 7 8 9 10 ] This potential association between maternal periodontitis and adverse pregnancy outcomes becomes an important concern because preterm birth and low birth weight are a major cause of infant mortality. [ 5 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Studies done in this field identified maternal periodontitis as a potential risk factor for preterm birth and low birth weight. [ 5 6 7 8 9 10 ] This potential association between maternal periodontitis and adverse pregnancy outcomes becomes an important concern because preterm birth and low birth weight are a major cause of infant mortality. [ 5 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Their results were in accordance with our results, they concluded that preexisting periodontal disease in the second trimester of pregnancy increases the risk of preterm labor with odds ratio of 4.45 to 7.07 for subjects with generalized periodontitis. Some interventional studies are also in support of our study [24][25][26], provided periodontal treatment before 28 weeks of gestation for 200 women compared to 200 women who were not treated, periodontal therapy during pregnancy was found to significantly reduces the rates of preterm labor and low birth weight in women with periodontal disease. They also concluded that periodontal disease was the strongest factor among other risk factors related to Preterm Labor and Low birth Weight odds ratio of 4.7.…”
Section: Discussionmentioning
confidence: 73%
“…These findings point to a blood-borne infectious pathway leading to direct fetal exposure as a major pathogenic mechanism of periodontitis associated with prematurity. [ 3 9 , 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these chemical mediators might be responsible intermediaries in developing adverse pregnancy outcomes. [ 10 ] In addition, increased gingival bleeding due to hormonal influence will aid in the entry of bacteria into the blood stream, which may enter uterus. [ 10 11 ]…”
Section: Discussionmentioning
confidence: 99%